Cloning and analysis of the genes encoding the type IIS restriction-modification system HphI from Haemophilus parahaemolyticus. - Lubys, A (1996)
The genomic region encoding the type IIS restriction-modification (R-M) system HphI (enzymes recognizing the asymmetric sequence 5'-GGTGA-3'/5'-TCACC-3') from Haemophilus parahaemolyticus were cloned into Escherichia coli and sequenced. Sequence analysis of the R-M HphI system revealed three adjacent genes aligned in the same orientation: a cytosine 5 methyltransferase (gene hphIMC), an adenine N6 methyltransferase (hphIMA) and the HphI restriction endonuclease (gene hphIR). Either methyltransferase is capable of protecting plasmid DNA in vivo against the action of the cognate restriction endonuclease. hphIMA methylation renders plasmid DNA resistant to R.Hindill at overlapping sites, suggesting that the adenine methyltransferase modifies the 3'-terminal A residue on the GGTGA strand. Strong homology was found between the N-terminal part of the m6A methyltransferasease and an unidentified reading frame interrupted by an incomplete gaIE gene of Neisseria meningitidis. The HphI R-M genes are flanked by a copy of a 56 bp direct nucleotide repeat on each side. Similar sequences have also been identified in the non-coding regions of H.influenzae Rd DNA. Possible involvement of the repeat sequences in the mobility of the HphI R-M system is discussed.